THE ROLE OF GAMES IN THE LANGUAGE TEACHING LESSONS - O’sarova, Nilufar (Журнал иностранных языков и лингвистики, 2021)
The article describes in detail methodological principles of games in teaching language and learning. It is discussed the importance of games and educational progress with the help of various activities in language teaching. It is widely explained about the benefits of using games in language-learning and summed up in nine points.